PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS VII SMPN 25 PADANG - Shalina, Ella Tirta (Jurnal Edukasi dan Penelitian Matematika, 2024)
Problem solving skills are very important skills for students to achieve learning objectives. Based on observations in class VII at SMPN 25 Padang show that students mathematical problem solving skills are still low. This study analyzes how the effect of the STAD type cooperative learning on improving problem solving skills. STAD type cooperative learning model was chosen according to questionnaire filled out by students that showed that more than 70% of students agreed with group learning. This research type is quasi-experimental research with a Non-equivalent Posttest Only Control Group Design. The sampling was carried out by simple random sampling and obtained class VII 3 as the experiment class and class VII 2 as the control class. Based on the results of data analysis showing that the P-value is lower than the significance level (?), the alternative hypothesis (H1) is accepted. This indicate that the STAD type cooperative learning model improves the students problem solving skills.Keywords– Student Teams Achievement Divisions, Problem Solving, Direct Learning